A Rare Case of Acute Renal Failure Secondary to Rhabdomyolysis Probably Induced by Donepezil - Osman Zikrullah Sahin; Teslime Ayaz; Suleyman Yuce; Fatih Sumer; Serap Baydur Sahin (Case Reports in Nephrology)
Introduction. Acute renal failure (ARF) develops in 33% of the patients with rhabdomyolysis. The main etiologic factors are alcoholism, trauma, exercise overexertion, and drugs. In this report we present a rare case of ARF secondary to probably donepezil-induced rhabdomyolysis. Case Presentation. An 84-year-old male patient was admitted to the emergency department with a complaint of generalized weakness and reduced consciousness for two days. He had a history of Alzheimer’s disease for one year and he had taken donepezil 5 mg daily for two months. The patient’s physical examination revealed apathy, loss of cooperation, and decreased muscle strength. Laboratory studies revealed the following: urea: 128 mg/dL; Creatinine 6.06 mg/dL; creatine kinase: 3613 mg/dL. Donepezil was discontinued and the patient’s renal function tests improved gradually. Conclusion. Rhabdomyolysis-induced acute renal failure may develop secondary to donepezil therapy.